Surgical management options for childhood intracranial arachnoid cysts: a comparative study - Wael Abd Elrahman Ali Elmesallamy; Mohamed Elbana; Hassan Abaza; Mohammed Fahmy; Mahmoud M. Taha (Egyptian Journal of Neurosurgery)
Abstract Background The symptomatic and incidentally discovered childhood intracranial arachnoid cysts may make it challenging to define the best management option, which may be surgical or observational. The best surgical option is still in debate, either regarding the type or the indication of surgery. This study aims to evaluate cysto-peritoneal shunts, endoscopic fenestration, and our technique of microsurgical partial excision of the cyst wall with maintenance of subarachnoid patency as surgical treatment options for childhood intracranial arachnoid cysts. Results This retrospective study was performed to compare three surgical options for treatment of childhood intracranial arachnoid cysts during the period from January 2015 to October 2022, with a follow-up of at least one year. These options included a cysto-peritoneal shunt, endoscopic fenestration, and microsurgical patency of the subarachnoid space without basal fenestration. Clinical improvement rating and operative complications showed insignificant differences between the three surgical options; however, total disappearance of the arachnoid cysts was significantly associated with the microsurgical option (p = 0.0312). Conclusion Surgical management of childhood arachnoid cysts either by cysto-peritoneal shunt, endoscopic fenestration, or microsurgical techniques was efficient according to the accessibility of the cysts, and the microsurgical patency of the subarachnoid space had the most significant effect on the disappearance of the cysts.